Clinical symptoms of combined abdominal and thoracic trauma in peacetime - Chaika, V.O.; Karpenko, S.I.; Zavizion , E.M. (Medicni Perspektivi, 2024)
Combined thoracic and abdominal trauma is considered one of the most severe in the structure of polytrauma, which causes a high frequency of complications – 33-72% and a mortality rate of up to 34%. The purpose of the study was to ensure the quality of the provision of medical services to victims with combined abdominal and thoracic trauma, through clinical assessment of the most significant symptoms and systematization of their manifestations aimed at justifying diagnostic and treatment measures. We conducted a prospective analysis of clinical manifestations in 44 victims with combined abdominal and thoracic trauma, who were treated at the city clinical hospital 16 of Dnipro in the period from 2019 to 2023. The average age of the victims was 41.5±2.4 years, men predominated – 40 (90.9%) people. In 40 (90.9%) victims, only 2 anatomical sites were damaged, 3 anatomical sites were damaged in 3 (6.8%) victims, 4 or more anatomical sites were damaged in 1 (2.3%) injured person. All victims were operated on. Multiple injuries of abdominal organs were observed in 14 (31.2%) victims. Among the injuries of the chest cavity, the most common cause was a lung contusion – 36.4% of cases. Exclusion criteria from the study were craniocerebral injury and contusion or injury to the heart as components of a combined injury. Also, the study did not include victims who received resuscitation measures during admission or at the stage of emergency care. Collection of complaints and anamnesis, examination, palpation, percussion and auscultation were used as research methods. The obtained information made it possible to determine the sequence of use of hardware and instrumental diagnostic methods. For better systematization of clinical symptoms, the latter were divided into three components – abdominal, thoracic and hemodynamic. The most frequent complaint was pain in the abdomen and in the chest area, respectively 75.6% and 82.9%. In the structure of the hemodynamic component, the victims most often complained of a feeling of general weakness – 73.2%. The accuracy of the symptoms detected during the diagnosis of damage to the abdominal organs ranged from 6.8% (Kulenkampf's symptom) to 93.2% pain of the abdominal wall. The diagnostic accuracy of Rozanov's symptom, which indicated damage to the spleen was 68.2%. Despite the fact, that such a symptom as pain during palpation of the chest occurred in 81.8% of victims, its diagnostic efficiency remains quite low – 54.5%. On the other hand, such a symptom as bone crepitation, with an accuracy of 95.5%, allowed us to assert the presence of rib fractures in the victims and hint at the probability of injury to the chest or abdominal organs, which we observed in 44.4% and 88.9% of cases, respectively. Damage to the lungs was also ascertained due to the sufficiently high diagnostic accuracy of the auscultatory symptom – weakening of breathing – 70.5%. Hypotension below 90 mm Hg. (45%; 50%), tachycardia (81.8%; 59.1%) and pallor of the skin (56.8%; 65.9%) showed sufficiently high diagnostic accuracy during the diagnosis of possible intraabdominal and intrapleural bleeding, respectively. The combination of damage to the organs of the abdominal and thoracic cavities was characterized by multifaceted clinical manifestations and signs of multisymptoms. Most of the symptoms taken separately had low accuracy regarding the presence or absence of a certain intracavitary post-traumatic pathology (from 6.8% to 43.2%); however, the combination of several of them indicated the multiplicity of damage to the organs of the abdominal cavity (from 41.7% to 100%). The best diagnostic accuracy was shown by Rozanov's symptoms – 68.2%, which indicated damage to the spleen and crepitation of rib fragments – 95.5%, as well as auscultatory weakening of breathing – 70.5%, which indicated lung damage.